Characterization of Flakes Made in Corn Flour (Zea Mays) and Pumpkin (Cucurbita Moshcata) with Addition of Soybean Flour (Glicine Max) - Lucia Saraswati; Fauzan Azima; Daimon Syukri (Andalasian International Journal of Agricultural and Natural Sciences)
ABSTRACT